Strongly(Vλ, A, Δn(vm),p, q)-summable sequence spaces defined by modulus function and statistical convergence - Aiyub, Mohammad (Proyecciones (Antofagasta), 2025)
In this paper we introduce strongly (Vλ,A, Δn(vm),p, q)-summable sequences and give the relation between the spaces of strongly (Vλ,A, Δn(vm),p, q) -summable sequences and strongly (Vλ, A , Δn(vm), p , q)-summable sequences with respect to a modulus function when A =(a ik) is an infinite matrix of complex number, (Δn(mv)) is generalized difference operator, p = (p i) is a sequence of positive real numbers and q is a seminorm. Also we give the relationship between strongly (Vλ,A, Δn(vm),p, q) - convergence with respect to a modulus function and strongly Sλ(A, Δn(vm))- statistical convergence.